2019
DOI: 10.1242/jcs.229054
|View full text |Cite
|
Sign up to set email alerts
|

Tau interacts with SHP2 in neuronal systems and in Alzheimer's disease brains

Abstract: Microtubule-associated protein tau, an integral component of neurofibrillary tangles, interacts with a variety of signaling molecules. Previously, our laboratory reported that nerve growth factor (NGF)induced MAPK activation in a PC12-derived cell line was potentiated by tau, with phosphorylation at T231 being required. Therefore, we sought to identify a signaling molecule involved in the NGF-induced Ras-MAPK pathway that interacted with phospho-T231-tau. Here, we report that the protein tyrosine phosphatase S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Tau phosphorylation at T231 potentiated NGF-induced activation of ERK1/2 kinases, whereas phosphorylation at S214 or the PHF1 site (S396/S404) inhibited this signaling (Leugers and Lee, 2010 ; Leugers et al, 2013 ). Additional work suggested that these effects might involve a direct, activating protein-protein interaction between tau and SHP2 (Kim et al, 2019 ). Tau and SHP2 interacted in pulldown assays and both proteins were identified as components of a larger protein complex using proximity ligation assays (Kim et al, 2019 ).…”
Section: Tau Modulation Of Signaling Pathways Activated By Insulin and Neurotrophin Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tau phosphorylation at T231 potentiated NGF-induced activation of ERK1/2 kinases, whereas phosphorylation at S214 or the PHF1 site (S396/S404) inhibited this signaling (Leugers and Lee, 2010 ; Leugers et al, 2013 ). Additional work suggested that these effects might involve a direct, activating protein-protein interaction between tau and SHP2 (Kim et al, 2019 ). Tau and SHP2 interacted in pulldown assays and both proteins were identified as components of a larger protein complex using proximity ligation assays (Kim et al, 2019 ).…”
Section: Tau Modulation Of Signaling Pathways Activated By Insulin and Neurotrophin Receptorsmentioning
confidence: 99%
“…Additional work suggested that these effects might involve a direct, activating protein-protein interaction between tau and SHP2 (Kim et al, 2019 ). Tau and SHP2 interacted in pulldown assays and both proteins were identified as components of a larger protein complex using proximity ligation assays (Kim et al, 2019 ). Pseudophosphorylation at T231 in tau enhanced the interaction with SHP2 in cells compared to T231A tau (Kim et al, 2019 ).…”
Section: Tau Modulation Of Signaling Pathways Activated By Insulin and Neurotrophin Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of two SNPs (i.e., rs1801270 and rs1059234) in CDKN1A positively correlated with NFT aggregation in AD patients [49]. The binding of protein tyrosine phosphatase non-receptor type 11 (PTPN11) and MAPT promotes neurogenesis by activating nerve growth factor [52]. Besides, matrix metallopeptidase 9 (MMP9) is also suggested to play a part in neurogenesis and other biological processes such as hypertension, demyelination, and inflammatory response [53,54].…”
Section: Comorbidity In Ad and T2dm Explained By Mechanistic Bel Graphsmentioning
confidence: 99%